Daily field checking list by Walter Rosene, May 23, 1935 - Rosene, Walter M., Sr., 1880-1941et al; Iowa Ornithologists' Unionet al
Bird checklist dated May 23, 1935. This checklist was used by Walter Rosene to record birds sighted around the Ledges with Bob Walker between 1:20 and 6:20. Plustek--flatbed